KAJIAN TEKNIS PEMBESARAN UDANG VANAME (Litopenaeus vannamei) SECARA INTENSIF DI TAMBAK UDANG BPBAP SITUBONDO - Ach. Khumaidi; Abdul Muqsith; Abdul Wafi; Ismi Jasila; Talkhis Hikam (Universitas Muhammadiyah Gresik, 2022)
The purpose of this study was to determine the intensive technique of rearing vannamei shrimp in shrimp hatchery installation Gelung, Brackish Water Aquaculture Center Situbondo, East Java. The data collection method used in this activity is a descriptive method that is the method carried out by looking at existing activites in the field with existing libraries. Activites undertaken include; pond preparation namely cleaning and washing of cultivation facilities, drying, HDPE plastic repair, map sterilization, installation of cultivation facilities and calcification of maps, preparation of aquaculture media including water filling and sterilization, fertilizer and POC application; selection and stocking of fry; feed management includes the type of feed, amount or dose of feed, frequency and technique of feeding, and check anco; water quality management includes observing water quality parameters, water change, water treatment and siphon; sampling; pest and disease control; harvest; and business analysis.